Violence and Visibility in Modern History - Martschukat, Jürgen.; Martschukat, Jürgen.; Niedermeier, Silvan.; Niedermeier, Silvan. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Despite the claims of Steven Pinker and others, violence has remained a historical constant since the Enlightenment, even though its forms and visibility have been radically transformed. Accordingly, the studies gathered here recast debate over violence in modern societies by undermining teleological and reassuring narratives of progress.